Pemenuhan Gizi Protein Hewani untuk Balita Rawan Stunting di Desa Binaan PT. Hindoli Cargill Melalui Program Budidaya Ikan dalam Ember (Budidamber): Pemenuhan Gizi Protein Hewani untuk Balita Rawan Stunting di Desa Binaan PT. Hindoli Cargill melalui Program Budidaya Ikan dalam Ember (Budidamber) - Marta Tika Handayani; Madyasta Anggana Rarassari; raudhatus saadah; Alan Novi Tompunu; Nelly Masnila (Universitas Muhammadiyah Palembang, 2025)
Stunting is currently the main nutritional problem that occurs in toddlers. The impact can be seen in the disruption of children's growth and development, and in the long term, this nutritional problem can reduce the quality of human resources in Indonesia. Through the Fish Cultivation in Buckets (Budidamber) program, this is an innovation in the form of environmentally friendly cultivation techniques. The aim of this service activity is to meet the nutritional needs of animal protein for toddlers prone to stunting in the village of Teluk Tenggulang, Tungkal Ilir, Banyuasin through the Fish Cultivation in Buckets (Budidamber) program. The target to be achieved is that the community in Teluk Teggulang Village who have toddlers prone to stunting can meet their nutritional needs for animal protein through the Budidamber Program so that these toddlers will experience weight gain. The strategy used to achieve the goal is by conducting field surveys, providing Budidamber packages to families who have toddlers prone to stunting, providing education on how to cultivate Budidamber, and monitoring Budidamber activities so that the program can run and the results of fish farming can be enjoyed by families who are given the Budidamber package. The results obtained from this program are an increase in partners' knowledge and skills regarding cultivating fish in buckets (Budidamber), an increase in food independence for families with stunting-prone toddlers and an increase in the weight of toddlers who are stunting-prone.